Reprogramming of plant cells by filamentous plant‐colonizing microbes. Issue 4 (24th July 2014) - Doehlemann, Gunther; Requena, Natalia; Schaefer, Patrick; Brunner, Frederic; O'Connell, Richard; Parker, Jane E.
Summary Although phylogenetically unrelated, filamentous oomycetes and fungi establish similar structures to colonize plants and they represent economically the most important microbial threat to crop production. In mutualistic interactions established by root‐colonizing fungi, clear differences to pathogens can be seen, but there is mounting evidence that their infection strategies and molecular interactions have certain common features. To infect the host, fungi and oomycetes employ similar strategies to circumvent plant innate immunity. This process involves the suppression of basal defence responses which are triggered by the perception of conserved molecular patterns. To establish biotrophy, effector proteins are secreted from mutualistic and pathogenic microbes to the host tissue, where they play central roles in the modulation of host immunity and metabolic reprogramming of colonized host tissues. This review article discusses key effector mechanisms of filamentous pathogens and mutualists, how they modulate their host targets and the fundamental differences or parallels between these different interactions. The orchestration of effector actions during plant infection and the importance of their localization within host tissues are also discussed.